Improving Students Speaking Skill Using Round Table Method at SMPN 3 Kopang - Salman, Salman (BAHTRA: Pendidikan Bahasa dan Sastra, 2023)
The aim of this research is to determine the impact of the Round Table method on improving students' speaking skills at SMPN 3 Kopang. In this research, researcher used Classroom Action Research by Kemmis and MC Taggart as the research design. This research was carried out in two cycles, each cycle consisting of planning, implementation, observation and reflection. Data collection was carried out by observation and tests. Data were analyzed using quantitative and qualitative analysis. The research results show that the application of the Round Table Method can improve students' speaking abilities. This is proven by student achievement through the Minimum Completion Criteria (MMC) (70) with a success indicator (70%) in cycle 2 results where 95% of students achieved a score of 70 or higher, while only 5% scored below 70. The highest post-test score was 92, and the lowest was 60, with an average score of 80.32. The percentage increase in students from post-test cycle 1 to cycle 2 was 33%. Not only students' grades, this learning method also improves students' attitudes/activities at every meeting during the learning process. Thus, it can be concluded that the Round Table Method can improve the speaking skills of seventh grade students at SMPN 3 Kopang.